2012
DOI: 10.1088/1468-6996/13/6/064214
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization and cytocompatibility evaluation of silanized magnesium alloy AZ91 for biomedical applications

Abstract: Mg alloys with high Al contents have superior corrosion resistance in aqueous environments, but poor cytocompatibility compared to that of pure Mg. We have silanized the cast AZ91 alloy to improve its cytocompatibility using five different silanes: ethyltriethoxysilane (S1), 3-aminopropyltriethoxysilane (S2), 3-isocyanatopyltriethoxysilane (S3), phenyltriethoxysilane (S4) and octadecyltriethoxysilane (S5). The surface hydrophilicity/hydrophobicity was evaluated by water contact angle measurements. X-ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…The authors showed that surfaces coated with MPTMS-diatoms improved vitality and shape of the two cells lines compared to surfaces coated with simple bare diatoms. On the other hand, on surfaces coated with APTES-diatoms, the external amino groups negatively affected both the adherence and proliferation of the two cell lines, consistent with previously reported results on interactions of cell surfaces with cationic nanoparticles [42,43,44]. While surface coating with diatoms plays a crucial role in tissue integration, it was soon recognized that natural biosilica from diatoms also offers a promising biocompatible material for medicinal applications.…”
Section: Diatoms As a Natural Biocompatible Materials For Therapeutsupporting
confidence: 88%
“…The authors showed that surfaces coated with MPTMS-diatoms improved vitality and shape of the two cells lines compared to surfaces coated with simple bare diatoms. On the other hand, on surfaces coated with APTES-diatoms, the external amino groups negatively affected both the adherence and proliferation of the two cell lines, consistent with previously reported results on interactions of cell surfaces with cationic nanoparticles [42,43,44]. While surface coating with diatoms plays a crucial role in tissue integration, it was soon recognized that natural biosilica from diatoms also offers a promising biocompatible material for medicinal applications.…”
Section: Diatoms As a Natural Biocompatible Materials For Therapeutsupporting
confidence: 88%
“…Moreover, from a recent and specific study on correlation between cell viabilities and surface functionalization of silanized magnesium alloy, the amino group has been again reported to negatively promote cell adhesion and proliferation of Saos-2 cells, likely due to a supposed massive albumin subtraction from cell media [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, frustules modified with amino groups hindered cell adhesion and proliferation. Amino groups have been reported to reduce cell adhesion and proliferation due to a supposed massive albumin subtraction from the cell media [85]. These results highlight the need to find the right functionalization strategy to promote cell growth on diatom-derived substrates and encourages the study of this material for further in vivo applications.…”
Section: Diatom As a Promising Scaffold For Cell Proliferation And Differentiationmentioning
confidence: 91%